Highly Porous Free-Standing rGO/SnO(2) Pseudocapacitive Cathodes for High-Rate and Long-Cycling Al-Ion Batteries - Jahnke, Timotheus (Nanomaterials (Basel), 2020)
Establishing energy storage systems beyond conventional lithium ion batteries requires the development of novel types of electrode materials. Such materials should be capable of accommodating ion species other than Li(+), and ideally, these ion species should be of multivalent nature, such as Al(3+). Along this line, we introduce a highly porous aerogel cathode composed of reduced graphene oxide, which is loaded with nanostructured SnO(2). This binder-free hybrid not only exhibits an outstanding mechanical performance, but also unites the pseudocapacity of the reduced graphene oxide and the electrochemical storage capacity of the SnO(2) nanoplatelets. Moreover, the combination of both materials gives rise to additional intercalation sites at their interface, further contributing to the total capacity of up to 16 mAh cm(−3) at a charging rate of 2 C. The high porosity (99.9%) of the hybrid and the synergy of its components yield a cathode material for high-rate (up to 20 C) aluminum ion batteries, which exhibit an excellent cycling stability over 10,000 tested cycles. The electrode design proposed here has a great potential to meet future energy and power density demands for advanced energy storage devices.